Accountability from the perspective of Malaysian governance - Yaakob, Ahmad Faiz; A. Kadir, Nadrah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Generally, accountability is often associated with a concept of answerability, responsibility, blameworthiness, liability etc. Commonly, the concept of accountability from the perspective of governance is the means to control the public administration in democratic countries. The classification of public accountability is normally seen in terms of external and internal mechanisms. Hence, this paper shall discuss both mechanisms with special reference to Malaysia. The discussion also focuses on the limitation of each mechanism which rendered some problems to the concept of accountability in Malaysia.